Sponsor RANCANG BANGUN PLATFORM SPONSORSHIP BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPING - Fajri Muttaqien; Ardianto Wibowo (ABEC Indonesia, 2021)
Sponsorship is a form of material or financial support by a sponsored provider for an organization, or event. But in reality it is based on the results of the questionnaires that have been distributed to 332 respondents who are members of event organizers, organizations, UKM (Student Activity Unit), HIMA (Student Association), and Community. As much as 87.2% stated that it was difficult to get sponsors for activities. This is due to the long process of applying for sponsorship, lack of information about the forms of sponsorship provided by sponsorship providers. Meanwhile, according to the sponsored provider, the problem is the difficulty in obtaining information on activities that match the needs of the sponsored provider. Therefore, with the Design of Website-Based Sponsorship Platform using the Prototyping Method which can connect event organizers in submitting sponsorship of the event to sponsor providers. Vice versa, the sponsored provider can also choose which event suits the needs of the sponsored provider is expanding the product brand. This system is designed using the Codeigniter Framework, the PHP programming language, and MYSQL as its DBMS. After testing the blackbox, it can be concluded that the sponsorship platform's functionality has been successful. For usability testing, there were 4 candidates for event organizers and 4 candidates for sponsor providers who often collaborated with sponsorships, the result was that 93.5% of users strongly agreed that this system was built. Keywords: Sponsorship, Organizations, Sponsor Providers, Events